Cognitive complaints and predictors of perceived cognitive dysfunction in adults with major depressive disorder: Findings from the Cognitive Dysfunction in Asians with Depression (CogDAD) study - Srisurapanont, Manit; Mok, Yee Ming; Yang, Yen Kuang; Chan, Herng Nieng; Della, Constantine D.; Zainal, Nor Zuraida; Jambunathan, Stephen; Amir, Nurmiati; Kalita, Pranab (Elsevier, 2018)
Background: Several studies have described the presence of perceived cognitive dysfunction amongst Asian patients with major depressive disorder (MDD). To date, no study has been conducted investigating the predictors of perceived cognitive dysfunction amongst Asian MDD patients. Methods: This was a post-hoc analysis of the Cognitive Dysfunction in Asian patients with Depression (CogDAD) study. Descriptive statistics were used to describe the most common cognitive complaints by patients. Univariate and multivariate analyses were performed to determine variables associated with perceived cognitive dysfunction (Perceived Deficit Questionnaire-Depression, PDQ-D). Results: The CogDAD study population is comprised of MDD patients with mild-to-moderate depression (Patient Health Questionnaire 9-item [PHQ-9]: 11.3 ± 6.9) who reported perceived cognitive dysfunction (PDQ-D = 22.6 ± 16.2). The most common cognitive complaints were: mind drifting (42.3%), trouble making decision (39.6%) and trouble concentrating (38.0%). Predictors of perceived cognitive dysfunction were: being Southeast Asians (vs. Taiwanese) (p < 0.001), current episode longer than 8 weeks (vs. 1–8 weeks) (p < 0.05), the presence of disability (vs. no disability) (p < 0.05), younger age (p < 0.01), and higher PHQ-9 total scores (p < 0.001). Limitations: The causal relationship between predictive variables and PDQ-D could not be tested due to the cross-sectional nature of the study. Furthermore, a neuropsychological test was not included in the CogDAD study and use of concomitant medications, including anti-depressants, could have impacted patient's perceived cognitive ability. Conclusions: The present study results suggest a potential role for subjective cognitive assessment in patients with MDD who are young, with long durations of depression or severe depression.